Application of Distilled Liquid Smoke on the Chemical Characteristics of Skipjack Fish Sausage - Bora, Naema; Bunga, Senni J. (The University of Lampung, 2024)
Smoked sausage is a popular food among people due to its distinctive aroma and taste. Generally, smoked sausages are made using traditional smoking methods. Since the advent of liquid smoke technology, the processing of smoked fish sausages can be done more practically and safely by immersing them in liquid smoke. The aim of this research was to determine the effect of the application of liquid smoke quality and liquid smoke concentration on the chemical characteristics of liquid smoked skipjack tuna sausage. The experiment was executed using a factorial CRD (Completely Randomized Design) with two factors: the quality of liquid smoke, consisting of grade 1, grade 2, and grade 3; and the concentration, consisting of 15%, 25%, and 35% by volume. The results of the study showed that the quality of liquid smoke grades 2, along with a liquid smoke concentration of 25%, can significantly increase the water content, pH, protein content, total acid, and the texture of liquid smoked skipjack tuna fish sausage. Keywords: Chemical characteristics, Fish sausage, Liquid smoke, Distilled liquid smoke.